Prevalence, Antimicrobial Susceptibility, and Molecular Characterization of Escherichia coli Isolated From Raw Milk in Dairy Herds in Northern China - Liu, Huimin; Meng, Lu; Dong, Lei; Zhang, Yangdong; Wang, Jiaqi; Zheng, Nan (Frontiers in Microbiology, 2021)
Escherichia coli is a common bacterium in the intestines of animals, and it is also the major important cause of toxic mastitis, which is an acute or peracute disease that causes a higher incidence of death and culling of cattle. The purpose of this study was to investigate E. coli strains isolated from the raw milk of dairy cattle in Northern China, and the antibacterial susceptibility of these strains and essential virulence genes. From May to September 2015, 195 raw milk samples were collected from 195 dairy farms located in Northern China. Among the samples, 67 (34.4%) samples were positive for E. coli. 67 E. coli strains were isolated from these 67 samples. The prevalence of STEC, ETEC, EPEC, and EIEC were 9, 6, 4.5, and 1.5%, respectively. Among the virulence genes detected, stx1 was the most prevalent (6/67, 9%) gene, followed by eae (3/67, 4.5%), and estB (2/67, 3%). Moreover, the strains exhibited different resistance levels to ampicillin (46.3%), amoxicillin-clavulanic acid (16.4%), trimethoprim-sulfamethoxazole (13.4%), tetracycline (13.4%), cefoxitin (11.9%), chloramphenicol (7.5%), kanamycin (7.5%), streptomycin (6.0%), tobramycin (4.5%), azithromycin (4.5%), and ciprofloxacin (1.5%). All of the E. coli isolates were susceptible to gentamicin. The prevalence of β-lactamase-encoding genes was 34.3% in 67 E. coli isolates and 45% in 40 β-lactam-resistance E. coli isolates. The overall prevalence of blaSHV, blaTEM, blaCMY, and blaCTX-M genes were 1.5, 20.9, 10.4, and 1.5%, respectively. Nine non-pathogenic E. coli isolates also carried β-lactamase resistance genes, which may transfer to other pathogenic E. coli and pose a threat to the farm’s mastitis management projects. Our results showed that most of E. coli were multidrug resistant and possessed multiple virulence genes, which may have a huge potential hazard with public health, and antibiotic resistance of E. coli was prevalent in dairy herds in northern China, and ampicillin should be used cautiously for mastitis caused by E. coli in Northern China.